2015
DOI: 10.1111/pcn.12294
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone long‐acting injection and 1‐year rehospitalization rate of schizophrenia patients: A retrospective cohort study

Abstract: Aims:We wanted to present a picture of patients with schizophrenia receiving risperidone long-acting injection (RLAI) treatment in a real-world setting.Methods: This was a retrospective cohort study; 379 patients with schizophrenia were enrolled and treated with different kinds of antipsychotic agents at E-Da Hospital, and received a 12-month follow up. The patients were distributed into three groups: the all-oral antipsychotic, oral risperidone and RLAI groups. The antipsychotic agents and dosages they used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…Finally, only the study by [ 69 ] presented results on the effectiveness of LAI risperidone in a retrospective cohort study vs. all-oral SGAs and FGAs and vs. oral risperidone [ 69 ]. All the studies, including patients treated with PP1M, reported significant improvements in subjective well-being and global satisfaction, and improved personal and social performance [ 59 , 65 , 67 , 68 , 70 , 71 , 72 , 74 , 75 , 76 , 78 , 79 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, only the study by [ 69 ] presented results on the effectiveness of LAI risperidone in a retrospective cohort study vs. all-oral SGAs and FGAs and vs. oral risperidone [ 69 ]. All the studies, including patients treated with PP1M, reported significant improvements in subjective well-being and global satisfaction, and improved personal and social performance [ 59 , 65 , 67 , 68 , 70 , 71 , 72 , 74 , 75 , 76 , 78 , 79 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…We adopted a within-individual comparison because people with schizophrenia often switched antipsychotic medications, and traditional cohort studies using between-individual comparison could not overcome this misclassification bias. 12 , 14 , 15 , 16 , 17 , 21 Selection bias is another problem in between-individual comparison because substantial differences exist in the inherent characteristics (eg, adherence) of patients prescribed LAIAs and patients prescribed OAs. 12 , 14 , 15 , 16 , 17 , 21 Within-individual comparisons could overcome this problem and only time-varying confounders need to be adjusted.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 14 , 15 , 16 , 17 , 21 Selection bias is another problem in between-individual comparison because substantial differences exist in the inherent characteristics (eg, adherence) of patients prescribed LAIAs and patients prescribed OAs. 12 , 14 , 15 , 16 , 17 , 21 Within-individual comparisons could overcome this problem and only time-varying confounders need to be adjusted. Although 1 Korean study 18 has applied a within-individual comparison, no adjustments for the time-varying confounders were made, and misclassification bias also existed because people receiving combined LAIA and OA therapy were categorized as exposed to LAIAs and compared with OA monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramuscular depot injections of long-acting antipsychotic medications are commonly administered to patients with schizophrenia (Berwaerts et al 2015;Chan et al 2015;Manchanda et al 2013;Rossi et al 2012;Schooler 2003). Because most long-acting injectable antipsychotic medications are oily suspensions of large volume, they are commonly prescribed for gluteal intramuscular injection (Gillespie & Toner 2013).…”
Section: Introductionmentioning
confidence: 99%